A Janus Smart Window for Temperature-Adaptive Radiative Cooling and Adjustable Solar Transmittance - Zhang, Zuowei; Yu, Meina; Ma, Cong; He, Longxiang; He, Xian; Yuan, Baohua; Zhang, Luoning; Zou, Cheng; Gao, Yanzi; Yang, Huai (Nano-Micro Letters, 2025)
The advancement of sophisticated smart windows exhibiting superior thermoregulation capabilities in both solar spectrum and long-wave infrared range maintains a prominent objective for researchers in this field. In this study, a Janus window is proposed and prepared based on polymer-stabilized liquid–crystal films/thermochromic materials. It can achieve switchable front long-wave infrared emissivity (εFront) and solar modulation ability (ΔTsol) through dynamic flipping, making it suitable for different seasonal energy-saving requirements. Outdoor experiments show that under daytime illumination, the indoor temperature decreases by 8 °C, and the nighttime temperature drops by 5 °C. MATLAB simulation calculations indicate that the daytime cooling power is 93 W m−2, while the nighttime cooling power reaches 142 W m−2. Interestingly, by modifying the conductive layer, it can effectively shield electromagnetic radiation (within the X-band frequency range (8.2–12.4) GHz). Energy simulation reveals the substantial superiority of this device in energy savings compared with single-layer polymer-stabilized liquid crystal, poly(N-isopropyl acrylamide), and normal glass when applied in different climate zones. This research presents a compelling opportunity for the development of sophisticated smart windows characterized by exceptional thermoregulation capabilities. Highlights: 1 Using polymer-stabilized liquid crystal as the active control layer and KCWO-PNIPAM (KPP) as the passive control layer, a KPP smart window was constructed, successfully achieving dual electro-thermal collaborative control. 2 The window can adjust incident light across three bands: visible light, near-infrared light, and mid-far infrared light (especially 8–13 µm). 3 Combination of active and passive control to meet the diverse weather conditions.